Genes IX / Benjamin Lewin - Lewin, Benjamin
This user-friendly, new Ninth Edition boasts a fresh modern design and contemporary art program, as well as a new organization which allows students to focus more sharply on individual topics. Thoroughly updated throughout, including a new chapter on Epigenetic Effects.